EKRANISASI NOVEL DANUR KARYA RISA SARASWATI DENGAN FILM DANUR SUTRADARA AWI SURYADI - Tri Widi Astuti; Khusnul Hafidiyanti; Nurul Setyorini (Kajian Linguistik dan Sastra, 2019)
This article discusses excarnation of the novel Danur by Risa Saraswati in comparison to the movie Danur directed by Awi Suryadi. The aims of this research is first to describe the addition within the novel Danur into the movie with the same title. Second, this research seeks for the reduction of the movie, and third, the change in variation of the adaptation movie. The main source of the article are the two object, namely the novel Danur by Risa Saraswati and the movie Danur directed by Awi Suryadi. The findings of this research suggest that there are an addition of characters and setting, reduction of characters and setting, and changes in the plot within the adaptation movie.  Keywords: Danur, novel, movie, structural narratives